Antibodies to the Vi capsule of Salmonella Typhi in the serum of typhoid patients and healthy control subjects from a typhoid endemic region. - House, D; Ho, V; Diep, T; Chinh, N; Bay, P; Vinh, H; Duc, M; Parry, C; Dougan, G; White, N; Farrar, J; Hien, T; et al. (2008)
BACKGROUND: There is very little published data on the antibody response to the Vi capsular polysaccharide (Vi-CPS) of S. Typhi during naturally acquired typhoid fever in an endemic area. METHODOLOGY: An indirect ELISA, using tyraminated, purified Vi-CPS, was used to assay anti-Vi-CPS antibodies from typhoid fever cases and controls living in the Ho Chi Minh City and Mekong Delta region of Viet Nam. RESULTS: Antibody response to Vi-CPS is significantly higher in typhoid patients who have been ill for more than two weeks than those who are in the first two weeks of illness. The anti-Vi-CPS response is similar for adults and children. Anti-Vi-CPS antibodies can be detected in the sera of non-typhoid patients. The frequency with which this occurs increases with age, probably reflecting increased exposure to S. Typhi. CONCLUSIONS: Anti-Vi_CPS is elicited in persons infected with S. Typhi but only after a prolonged duration of illness. Vaccine trials have shown anti-Vi-CPS antibodies to be protective; thus early treatment of typhoid patients, i.e. in the first two week of illness before the Vi-CPS response is elicited, may inhibit the development of this protective immune response.